COVID-19 and antimicrobial stewardship: lessons learned, best practices, and future implications. (December 2021) - Pierce, Jacob; Stevens, Michael P.
Highlights: Empiric antibiotic use is higher than rates of bacterial co-infection with COVID-19. Stewardship programs should play a role in limiting unnecessary antimicrobial use. Stewardship program infrastructure can be used in COVID-19 pandemic relief efforts. Data on stewardship activities focused on COVID-19 relief are limited. Abstract: The coronavirus disease 2019 (COVID-19) pandemic has had a profound and often devastating impact on global healthcare systems. Healthcare systems have had to repurpose programs and staff as part of COVID-19 relief efforts. The infrastructure and skilled personnel of antimicrobial stewardship programs (ASPs) have been utilized in new ways as part of COVID-19 pandemic response efforts. A critical focus of ASPs both before and during the pandemic has been on limiting the development of antimicrobial resistance. Fortunately, existing data indicate that rates of bacterial co-infection are relatively low and ASPs should continue aggressive efforts to limit unnecessary antimicrobial use. ASPs have taken a lead role in COVID-19 focused guideline creation and curation, as well as in helping to steward access to potential novel therapeutic agents. Disparities in ASP program resources and personnel exist, and ASP activities focused on the COVID-19 response should be tailored to individual settings. There is an urgent need for research to help inform ASP best practices within pandemic response efforts that take into account local resources. Investment in infrastructure and personnel is urgently needed both in the context of current relief efforts and to prepare for future pandemics.